2021
DOI: 10.3390/met11111851
|View full text |Cite
|
Sign up to set email alerts
|

Defectoscopic and Geometric Features of Defects That Occur in Sheet Metal and Their Description Based on Statistical Analysis

Abstract: Features of the defect class “scratches, attritions, lines”, their geometric structure, and their causes are analyzed. An approach is developed that defines subclasses within this class of technological defects based on additional analysis of morphological features. The analysis of the reasons for these subclasses allows additional information to be obtained about the rolling process, identifying additional signs of defects, regulating the rolling conditions of steel strips more accurately, and diagnosing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…First of all, the area was defined as the basic parameter that characterizes the damage size. To calculate other parameters, we used the "equivalent" ellipse approach (Figure 6) proposed by the authors of [10,[19][20][21][22]. The equivalent ellipse has a second moment equal to the moment of the defect recognized.…”
Section: Quantitative Parameters Of Damagementioning
confidence: 99%
See 1 more Smart Citation
“…First of all, the area was defined as the basic parameter that characterizes the damage size. To calculate other parameters, we used the "equivalent" ellipse approach (Figure 6) proposed by the authors of [10,[19][20][21][22]. The equivalent ellipse has a second moment equal to the moment of the defect recognized.…”
Section: Quantitative Parameters Of Damagementioning
confidence: 99%
“…Therefore, wherever it is necessary to identify the main, most pronounced damage, low light may be appropriate. At the same time, the noise level in the image caused by an increased level of detail with respect to surface formations, which may not represent damage, is much lower [21,22].…”
Section: Investigating the Influence Of Lighting On The Recognition R...mentioning
confidence: 99%
“…Modern investigations showed that neural network-based defect detection methods allow high accuracy to be reached in the recognition of different classes of surface defects [22][23][24]. However, investigating and streamlining neural networks' capabilities and limitations in detecting, classifying, and calculating the parameters of the most common group defects appear crucial [25][26][27].…”
Section: Introductionmentioning
confidence: 99%